ADOPTION OF MEDIA INNOVATIONS FOR MARKETING COMMUNICATIONS FOR UMKM FOR THE LATEST COLD DRINK IN THE DIGITALIZATION ERA - Husriadi, Muh.; M, Usman.; Mulya, La Ode Andi Rahmat; Ningsi, Citra Ayu (Maneggio, 2024)
The implementation of innovation in digital communication media by MSMEs in the cold beverage sector faces several significant challenges, including lack of technical knowledge, limited resources, and limited access to digital training. This study aims to investigate the effect of digital technology adoption on MSME business performance, especially in terms of increasing customer engagement, sales, and expanding market reach. The methodology applied is a qualitative approach through in-depth interviews with MSME owners in the cold beverage industry. The research results revealed that despite the challenges faced, the use of social media can increase interaction with customers, expand market reach beyond local areas, and increase sales by up to 40%. The findings of this study indicate that support in the form of digital training and access to resources is essential to optimize the use of digital media by MSMEs. Implementing the right digital strategy has the potential to strengthen the competitiveness of MSMEs amidst increasingly tight global market competition.